Liassic source rock deposition in western Europe. - Fleet, A; Clayton, C; Jenkyns, H; Parkinson, D (Graham and Trotman, 1987)
During Liassic times organic-rich mudstones - actual or potential petroleum source rocks - were deposited in many of the epicontinental basins of western Europe and along the adjacent protocontinental margins of the western Tethys Ocean. From Hettangian to Pliensbachian times organic-rich mudstones were deposited in geographically restricted basins which developed among a low-lying archipelago running from Ireland in the W to Germany in the E. These sediments, which were mostly oil-prone were deposited episodically. Their oil-prone character apparently resulted from stratification in the basins brought about by run-off from the archipelago forming a low-salinity layer over the basins. In the north, between Greenland and Scandinavia and throughout adjacent more southerly areas, gas-prone paralic and nearshore sediments were deposited throughout Liassic times. They reflect the large input of terrigenous biological and sedimentary detritus derived from the mountains of Greenland and Scandinavia. They reached their maximum extent at the time of maximum regression during the Sinemurian.- from Authors